Способ переработки отработавшего ядерного топлива - Гаврилов П. М. Петр Михайлович; Ревенко Ю. А. Юрий Александрович; Бараков Б. Н. Борис Николаевич; Бычков С. И. Сергей Иванович; Лапшин Б. М. Борис Михайлович; Алексеенко В. Н. Владимир Николаевич
опубл. 27.12.10